The Effects of Er Xian Decoction Combined with Baduanjin Exercise on Bone Mineral Density, Lower Limb Balance Function, and Mental Health in Women with Postmenopausal Osteoporosis: A Randomized Controlled Trial. (30th June 2022) - Li, Keqiang; Yu, Hongli; Lin, Xiaojun; Su, Yuying; Gao, Lifeng; Song, Minjia; Fan, Hongying; Krokosz, Daniel; Yang, Huixin; Lipowski, Mariusz
Abstract : Background . Postmenopausal osteoporosis (PMOP) is a common disease in older women that can severely jeopardize their health. Previous studies have demonstrated the effect of Er xian decoction (EXD) or Baduanjin exercise (BE) on PMOP. However, reports on the effect of EXD combined with BE on PMOP are limited. This study aimed to investigate the impact of EXD combined with BE on bone mineral density (BMD), lower limb balance, and mental health in women with PMOP. Methods . A 1 : 1 : 1 simple randomization technique was employed. Fifty participants with postmenopausal osteoporosis were allocated to three groups: the EXD group (EXD = 15); the BE group (BE = 18); and the combined group (EXD + BE = 17). After both 8 weeks and 16 weeks of intervention treatment, participants improved significantly with respect to BMD and the one-leg standing test (OLST), Berg balance scale (BBS), timed up and go (TUG) test, self-anxiety scale (SAS), and self-rating depression scale (SDS). The results were used to compare the effect of the intervention on BMD, lower limb balance function, and mental health in patients with PMOP. Results . Compared to the EXD and BE groups, the EXD + BE group showed the strongest effects on BMD, lower limb balance function, and mental health (p < 0.01 ). A correlation between BMD and lower limb balance and mental health was noted in the EXD + BE group. The change in mental health (SAS score) was correlated with BMD (femoral neck) improvement. Conclusions . The present study demonstrates that EXD combined with BE (EXD + BE) may have a therapeutic advantage over both monotherapies for treating BMD, lower limb balance function, and mental health in patients with PMOP. The feasibility of the approach for a large-scale RCT was also confirmed. Er xian decoction combined with Baduanjin exercise (EXD + BE) might offer a viable treatment alternative for participants with postmenopausal osteoporosis given its promising effects in disease control and treatment, with good efficacy and safety profiles.